Branching Process to Model the SARS-COV-2 in the City of Bogotá (2022)
The objective of the work is to implement a methodology for the description of the evolution of the SARS-CoV2 virus in the city of Bogotá. For this, a Galton Watson process is considered with two types of individuals: reported infected and unreported infected (asymptomatic). Only the daily statistics of Covid-19 cases reported by the Bogotá Health Secretariat are used to give a prediction of the mean value of the population contagious individuals. Finally, those individuals who arrive in Bogotá from other cities and even from other countries and who contribute to the spread of the virus are included in the model.